Pornography and civil rights: a new day for women's equality - Dworkin, Andrea; MacKinnon, Catharine A. (Organizing Against Pornography, 1988)
"Pornography is central in creating and maintaining the civil inequality of the sexes. Pornography is a systematic practice of exploitation and subordination based on sex which differentially harms women. . . ." With those bold words began the groundbreaking local antipornography law drafted by writer Andrea Dworkin and lawyer Catharine A. MacKinnon. Their completely new legal approach--in which pornography is defined as sex discrimination and therefore a violation of civil rights--would allow anyone injured by pornography to fight back by filing a civil lawsuit against pornographers. First passed in December 1983 in Minneapolis, where it was supported by a grassroots coalition of women, people of color, neighborhood groups, and the city's welfare poor and working poor, this law has transformed the way people of conscience understand the devastating impact of pornography on women's right to equality. This new law also offers hope: an effective legal tool for making sex equality real. In this comprehensive and easy-to-read guidebook, now available on line, the coauthors of the anti-pornography civil-rights ordinance explain: How pornography hurts women and how and why the civil-rights ordinance would make a difference. Why the pornography is so important to women's equality. The truth about the antipornography civil-rights ordinance--what it is, what it does, what it means, how it works. Answers to the lies about it--lies that the media have spread to protect the pornography industry. What you can do to stop the pornographers and further women's equality. "The Ordinance does not take 'rights' away from anyone, . . . it takes the power to hurt women away from pornographers." --from Pornography and Civil Rights
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; discipline; droit; droits des femmes*; féminisme anti-porn; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; science politique et droit; sex1911; sexualité; sofia; thématiques; violences; états-unis

Homeward bound: American families in the Cold War era - May, Elaine Tyler (Basic Books, 1988)
In the 1950s, the term "containment" referred to the foreign policy-driven containment of Communism and atomic proliferation. Yet in Homeward Bound May demonstrates that there was also a domestic version of containment where the "sphere of influence" was the home. Within its walls, potentially dangerous social forces might be tamed, securing the fulfilling life to which postwar women and men aspired. Homeward Bound tells the story of domestic containment - how it emerged, how it affected the lives of those who tried to conform to it, and how it unraveled in the wake of the Vietnam era's assault on Cold War culture, when unwed mothers, feminists, and "secular humanists" became the new "enemy." This revised and updated edition includes the latest information on race, the culture wars, and current cultural and political controversies of the post-Cold War era.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; amériques; approches et analyses; cold war; cours; discipline; division of household labor; division sexuelle du travail; famille; guerre froide; his4443; histoire; histoire des femmes*; histoire du féminisme; histoire et politique; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; thématiques; travail; travail domestique; états-unis